KERAGAAN KOPI PASAR DOMESTIK INDONESIA - Sagita, Taufani; Hidayati, Dwi Ratna (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2013)
ABSTRACTCoffee has been becoming one of priority commodity of Indonesia since this country also as one of main producer in the world. However, Indonesia got hardly in maintaining world position due to increasing of production and capacity of other country such as in Vietnam and Brazil. Therefore, it is necessary to recognize situation of demand and supply for coffee commodity in domestic scope to understand further theÂ bargaining position level. Various variable such as production, productivity,demand, supply, domestic price, export and import of coffe are considered to be performance variables for domestic market.Â This research used SAS (Statistical Analysis System) tool by using times series data. The result of the analysis shown that the performance of Indonesian coffee trading is affected by the supply, demand and price of Indonesian coffee.Keywords : coffee commodity, coffee demand, coffee supply,Â